Analyzing Technical Competency, Relational Capabilities and Cognitive Abilities on Customer Satisfaction at Distributor Companies in Indonesia - Mohamad Firdaus; Krisnawati, Nila; Basbeth, Firdaus (Emerging Markets : Business and Management Studies Journal, 2021)
In the current era of globalization, business competition is getting tougher and as a market leader, companies must always maintain their performance and improve their performance, so that customer satisfaction is always maintained. Especially the performance of mechanical services to customers whose performance must be maintained. Main problem faced by PT United Tractors heavy equipment service division is a decrease in customer satisfaction. The decrease in satisfaction is thought to be caused by a decrease in mechanics technical competence, the lack of mechanical ability to maintain good relationships (relational capability) with customers and the ability to identify problems (cognitive abilities) faced by customers. The purpose of this research is to analyze the impact of technical competency, relational capability and cognitive ability toward customer satisfaction and to analyse the impact of customer satisfaction toward customer loyalty. As a quantitative research, the study distributed questionnaires to 200 respondents who are customers who used mechanics services, so that it can be seen what variables have a significant impact on customer satisfaction. The findings of this study are that cognitive ability and technical competency have a significant impact on customer satisfaction, while relational capability has no significant impact on customer satisfaction. The influence of customer satisfaction on customer loyalty has a significant impact.